Coenzyme Q10 Improves Developmental Competence of Mice Pre_antral Follicle Derived From Vitrified Ovary - Hosseinzadeh, Elmira; Zavareh, Saeed; Lashkarboluki, Taghi (Archives of Advances in Biosciences, 2015)
The aim of this study was to investigate the in vitro developmental competence of isolated pre-antral follicles derived from vitrified ovaries in the presence of coenzyme Q10 (CoQ10). Mice pre-antral follicles derived from fresh and vitrified-warmed ovarian tissues were in vitro cultured individually in α-MEM medium supplemented with or without CoQ10, followed by adding human Chorionic Gonadotropin (hCG) to induce ovulation. The follicle development parameters and ovulated oocyte maturationwere assessed.The diameter and development of pre-antral follicles and oocyte maturation rates were significantly higher in CoQ10 pretreatment groups of both vitrified and fresh samples compared to the respective CoQ10free conditions groups. CoQ10 improves the in vitrodevelopment of pre-antral follicles derived from fresh and vitrified –warmed ovaries.